On the Search of a Hermeneutical Philosophy of the Political - Przylebski, Andrzej (My University, 2014)
My study can be considered as a part of my over 10-year research in the area of systematically spread out paradigm of hermeneutic philosophy. Briefly about that as I understand this philosophy. First of all, I do not equate it simply with hermeneutics. Because the latter is often understood either as a theory / methodology, containing rules that direct the art of interpretation (e.g., biblical or legal hermeneutics), or simply as a particular interpretation (e.g. hermeneutics Shakespeare’s "Hamlet"). Even Martin Heidegger, the founding father of hermeneutical philosophy, when he talks about the hermeneutics of facticity or on hermeneutics of Dasein (human being), he refers to a particular interpretation – his own interpretations of the human being, recognized as an existence. That is why I, while speaking of hermeneutical philosophy, am not referring to this particular idea of Heidegger. When I am speaking of hermeneutical philosophy I do not mean simply a theory of interpretation, because every self-respecting direction or philosophical school has such a theory, due to the career that category of interpretations made in the second half of twenty century. From neo-Kantianism, though pragmatism, the philosophy of life till structuralism, the analytic philosophy or deconstruction. Interpreting is such a widespread act that every serious philosophical trend must have some idea of it.
Keywords: Hermenéutica; Filosofía; Hermeneutical Philosophy; Politics